From Monotony to Motivation: Utilizing Differentiated Learning Materials in Teaching English to 11th Grade - Damayanti, Hemalia; Salsabila, Dya; Admajayanti, Fifian; Tawanggono, Ghandy Ardyan; Nurjamin, Lucky Rahayu (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2025)
This Classroom Action Research (CAR) study addressed the issue of low student motivation and limited oral communication skills in 11th-grade English language learning, stemming from the use of limited and monotonous learning materials and a rigid, textbook-driven pedagogical approach. Recognizing the crucial role of differentiated learning materials and effective pedagogical practices in fostering engagement and comprehension, this study implemented a series of interventions within two cycles. The action research process involved the introduction of differentiated learning resources, including educational videos, interactive learning apps, and online collaborative tools, integrated into the existing teaching modules, alongside explicit instruction on speaking strategies. Data were collected through classroom observations, student reflections, pre- and post-intervention speaking assessments, and an analysis of teaching module documents. The findings revealed a significant increase in student engagement, motivation, and oral communication skills following the implementation of diverse materials and targeted instruction. Students reported reduced boredom and a renewed interest in learning English. Furthermore, the speaking assessments demonstrated measurable improvements in both fluency and accuracy. Critically, the study also revealed a discrepancy between the intended Genre-Based Approach and the actual implementation in the teaching modules, highlighting the importance of teacher pedagogical understanding and the transformative potential of CAR for teacher development. This study underscores the effectiveness of incorporating differentiated learning materials, collaborative activities, and explicit instruction to enhance student motivation and improve learning outcomes within the context of 11th-grade English language education while also emphasizing the necessity of ongoing reflection and adaptation in pedagogical practices.